Edukasi Pengelolaan Sampah Anorganik Terhadap Pengetahuan Dan Sikap Masyarakat Desa Sirnajaya - Pamella M Sri Rezeki; Athaya Zhafirah; Rachminawati; Eko Walujodjati; Anjas Ninda Hantari; Ida Farida; Rina Kurniawati; Sulwan Permana; Dendi Yogaswara; Nanang; Adi Susetyaningsih; Ismi Purnamasari; Reski Ramadhani; Yeni Pariyatin; Alan Wijaya; Ratu Mafas Sukmalaras; Subhan Mulyana; Agus Ismail; Cepi Wendiki Alamsyah; Ganjar Jojon Johari; Greece Maria Lawalata; Madi Hermadi; Rudy Febrijanto; Fitri Nuraeni; R Dini Destiani Siti Fatimah; Risma Liyana Ulfa; Sri Rahayu (Institut Teknologi Garut, 2026)
Inorganic waste management remains a significant environmental challenge in rural areas. This Community Service Program (PkM) aimed to evaluate the effectiveness of an educational intervention on inorganic waste management in improving the knowledge and attitudes of residents in Sirnajaya Village, Garut. The program was conducted on February 4, 2026, in collaboration with the Garut Zero Waste community using a pre-test and post-test design involving 18 participants, consisting of housewives, university lecturers, and community members. The assessment instrument covered five indicators: understanding the definition of inorganic waste, identifying examples of inorganic waste, recognizing the environmental impacts of improper waste disposal, attitudes toward waste segregation, and intentions to reduce the use of single-use plastics. The results showed that 83.3% of the participants already possessed a high level of baseline knowledge. Consequently, the improvement in post-education scores was relatively limited, with an average normalized gain (N-Gain) of 0.11. This finding reflects a common ceiling effect, rather than indicating the ineffectiveness of the educational program. Nevertheless, three out of eighteen participants with lower initial knowledge demonstrated substantial improvements, achieving moderate to high levels of learning gain. Overall, the program contributed primarily to strengthening participants' knowledge and behavioral intentions regarding inorganic waste management. However, measurable changes in actual household waste management practices require further medium-term observation and follow-up evaluation.